2021
DOI: 10.1186/s13036-021-00262-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Activities and Applications of Bacterial Pigments Violacein and Prodigiosin

Abstract: In this review, we discuss violacein and prodigiosin, two chromogenic bacterial secondary metabolites that have diverse biological activities. Although both compounds were “discovered” more than seven decades ago, interest into their biological applications has grown in the last two decades, particularly driven by their antimicrobial and anticancer properties. These topics will be discussed in the first half of this review. The latter half delves into the current efforts of groups to produce these two compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 183 publications
1
33
0
Order By: Relevance
“…Crude extract mass from 3.0 L fermentation in NB was 0.66 g/L, affording 7.2 mg/L (1.1%) of PG as a dark red solid, suggesting high efficiency of the extraction and purification procedure. The molecular formula of the purified pigment was determined by HR-LC-ESI-MS at m/z 324.2098 [M+H] + to be C 20 H 25 N 3 O, corresponding to PG, and the chemical structure of purified PG was confirmed by 1 H-and 13 C-NMR spectroscopy (Figure S2), which was found to be identical to literature values [54].…”
Section: S Marcescens Atcc 27117 Cultivation For Prodigiosin Productionsupporting
confidence: 55%
See 1 more Smart Citation
“…Crude extract mass from 3.0 L fermentation in NB was 0.66 g/L, affording 7.2 mg/L (1.1%) of PG as a dark red solid, suggesting high efficiency of the extraction and purification procedure. The molecular formula of the purified pigment was determined by HR-LC-ESI-MS at m/z 324.2098 [M+H] + to be C 20 H 25 N 3 O, corresponding to PG, and the chemical structure of purified PG was confirmed by 1 H-and 13 C-NMR spectroscopy (Figure S2), which was found to be identical to literature values [54].…”
Section: S Marcescens Atcc 27117 Cultivation For Prodigiosin Productionsupporting
confidence: 55%
“…The method of choice for the estimation of the yield of PG is spectrophotometric measurement using the extinction coefficient ε 535 of 0.159 L/(mg × cm) and a conversion to the concentration using the Lambert-Beer law [12]. However, due to different extinction coefficients used for these calculations and the purity of compounds, the PG concentration can be overestimated even by 270% [13]. Nevertheless, developing methods for direct isolation, purification, and measurement of the biopigment mass is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Prodigiosin is a vibrant red, tripyrrole pigment produced by different bacterial strains, including Janthinobacterium ( 1 ) and Streptomyces ( 2 , 3 ), but is best characterized in Serratia marcescens ( 4 ), where the proteins responsible for its biosynthesis are encoded within the prodigiosin biosynthesis gene cluster ( pig ) ( 5 ). As a secondary metabolite, prodigiosin possesses a range of biological activities, as reviewed recently ( 6 ), but its antimicrobial activities are probably best known, with a number of bacterial pathogens reportedly being sensitive ( 6 9 ), including Bacillus cereus ( 10 ), Streptococcus pyogenes ( 11 ) and, in particular, Staphylococcus aureus ( 10 , 11 ). While the bactericidal mechanisms of prodigiosin, including the production of reactive oxygen species (ROS) ( 10 , 12 ), H + /CL − transporter uncoupling ( 13 ) and membrane disruption attributed to prodigiosin’s strong hydrophobic character ( 14 ), have all been explored by several different groups, they do not explain how this compound is conveyed from its host to other microorganisms, and is active in natural environments ( 15 17 ).…”
Section: Observationmentioning
confidence: 99%
“…Violacein has proved itself of commercial importance due to a range of biological and industrial activities. Many studies have shown that violacein exhibits multiple biological properties, e.g., anti-bacterial [13], anti-fungal [14], anti-cancer [16,17], antiviral properties [18], etc. In the following section, we review the latest advances on studies of its biological properties in detail, along with a brief summary in Table 3.…”
Section: Biological Activities Of Violacein/deoxyviolaceinmentioning
confidence: 99%